ZAMANAGÓY DÁSTÚRLEW TILLERI JÁRDEMINDE MOBIL QOSÍMSHALAR JARATÍW METODIKASÍ - Qunnazarov, A.Q. (SCIENCE and SOCIETY, 2024)
This article describes the requirements for modern languages and types of programming, their world ranking, the creation of mobile applications in Python, Java programming languages, and the creation of mobile applications.